2010
DOI: 10.5301/ejo.2010.6186
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Mutation in the PTCH Gene in a Patient with Gorlin-Goltz Syndrome with Unusual Ocular Disorders

Abstract: A novel nonsense mutation in the PTCH gene was found. We report the occurrence of epiretinal membranes and the persistence of myelinated nerve fibers. Electrophysiologic and visual field alterations, supporting a neuroretinal dysfunction, were also documented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“… 23 Though there is no definitive proof that Gorlin syndrome is the cause of these findings, the vitreous may be selectively affected in NBCCS due to the mesodermal origin and large proportion of collagen. 23 More recently, cases of bilateral epiretinal membranes, 24 bilateral macular holes, 25 and a combined hamartoma of the retina and retinal pigment epithelium (RPE) 26 in patients with NBCCS have been published. Mouse models of patched gene (PTCH) knockouts show photoreceptor dysplasia and secondary Muller cell-derived gliosis, 27 possibly explaining the link between the pathogenesis of Gorlin syndrome and these aberrant retinal findings.…”
Section: Ophthalmologic Findingsmentioning
confidence: 99%
“… 23 Though there is no definitive proof that Gorlin syndrome is the cause of these findings, the vitreous may be selectively affected in NBCCS due to the mesodermal origin and large proportion of collagen. 23 More recently, cases of bilateral epiretinal membranes, 24 bilateral macular holes, 25 and a combined hamartoma of the retina and retinal pigment epithelium (RPE) 26 in patients with NBCCS have been published. Mouse models of patched gene (PTCH) knockouts show photoreceptor dysplasia and secondary Muller cell-derived gliosis, 27 possibly explaining the link between the pathogenesis of Gorlin syndrome and these aberrant retinal findings.…”
Section: Ophthalmologic Findingsmentioning
confidence: 99%
“…[21][22][23] In this research, the analysis of VEP demonstrated an increase in latency as well as a reduction in amplitude in the observed patient, indicative of a qualitative and quantitative disorder of the optic pathway conduction (Figure 2). 19,24 The significant results, throughout all frequencies of spatial stimulation, suggest a dysfunction of the macular pathway in NBCCS patients compared to the CG.…”
Section: Discussionmentioning
confidence: 95%
“…25,26 Interestingly, the amplitude reduction and the significant increase of the latency in NBCCS group in the transmission time of the optical impulse may correlate to a subclinical myelin alteration in NBCCS. 14,19 Besides, we know that from a genetic point of view the activation of the SHH pathway is required for the development of the visual system. In fact, SHH expression is required for the induction of the optic nerve as well as photoreceptor differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PTCH1 / 2 mutations that have been identified in both BCN syndrome and HPE are usually missense variants and dominant, implying that additional haploinsufficiency also would be embryonic lethal in humans. A truncating, dominant germline mutation in PTCH1 was identified in one BCN syndrome patient with myelinated fibers and optic nerve anomalies in one eye and epiretinal membranes in both (Romano et al 2011). Another patient with a truncating PTCH1 mutation was reported with both BCN syndrome and unilateral microphthalmia with cyst (Ragge et al 2005b).…”
Section: Hedgehog Signaling In Early Brain and Ocular Pathogenesismentioning
confidence: 99%